Kitten chased a fly(windmill readers) - Randell, Beverley (Rigby Crystal Lake, 1998)
This early reader book introduces simple vocabulary and sentence structure, making it ideal for emerging readers. The captivating story of a playful kitten chasing a fly helps build confidence and fluency in reading.